2021
DOI: 10.1111/jppi.12386
|View full text |Cite
|
Sign up to set email alerts
|

State of the Field: The Need for Self‐Report Measures of Health and Quality of Life for People With Intellectual and Developmental Disabilities

Abstract: Background: Collecting self-reported health and quality of life (QoL) outcomes is increasingly considered best practice, but people with intellectual and developmental disabilities (IDD) are often excluded from patient-reported outcome measures.Objective: This article provides a literature-informed overview of the state of the field of self-reporting of physical health and QoL in research with adults with IDD.Approach: We first identified and synthesized definitions of key constructs related to the self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…This has direct implications for use of proxy‐reporting on health information for persons with IDD. Surveillance development needs to support autonomy by maximizing opportunities for persons with IDD to self‐report on surveys (Shogren et al, 2021). These differences exemplify the need to view people with IDD as “first among equals” when discussing their health and need for data.…”
Section: Discussionmentioning
confidence: 99%
“…This has direct implications for use of proxy‐reporting on health information for persons with IDD. Surveillance development needs to support autonomy by maximizing opportunities for persons with IDD to self‐report on surveys (Shogren et al, 2021). These differences exemplify the need to view people with IDD as “first among equals” when discussing their health and need for data.…”
Section: Discussionmentioning
confidence: 99%
“…One review of self-reported quality-of-life inventories among individuals with psychosis found that many measures were vague and had little evidence of psychometric quality [64]. Research concerning accessible assessment of PROs among populations that may struggle with attention, memory, or executive dysfunction suggests adapting design features to reduce assessment burden, such as giving specific examples or extra direction during administration, using visual aids where appropriate, or reducing cognitive demands by laying out measures in ways that reduce the need to visually scan and shift attention during administration [65,66]. Especially in populations where cognitive difficulties are common, care should be taken to ensure that participants adequately understand questionnaire items and that the layout, instructions, and response options of the measure are not overly burdensome.…”
Section: Recommendations For Eliciting Subjective Informationmentioning
confidence: 99%
“…It is plausible that previous studies that looked into empathic abilities in people with MID/BI used methods that do not fit for this group of people. For instance, it is known that individuals with MID/BI have problems with understanding negatively phrased items, long and complex sentences, abstract formulations, and that they have a limited vocabulary [ 20 , 21 ]. Furthermore, research has shown that people with MID/BI have problems answering questions with many options [ 20 ].…”
Section: Introductionmentioning
confidence: 99%